Enhancement of adversity quotient of houseparents of children in conflict with the law through solution-focused brief therapy - Mamauag, Charmaine Grace P.
"Houseparents are the most significant adult in the lives of Children in Conflict with the Law (CICL). However, there is not much research about them and their predicament. This study is conducted to identify the concerns of the houseparents which are grouped into bio-psychosocial, professional and skills development, employment, and equipment and facility, and to know the coping strategies they employ in facing the adversities they encounter considering the nature of their job and their clientele. The identified coping strategies are keeping distance from the child, resting, ignoring the child/ situation, talking with co-workers, breathing, smoking, writing in the logbook, enjoying recreational activities, eating, and venting out on the children are all classified as avoidant coping strategies. This study also sought to determine the effect of Solution-Focused Brief Therapy (SFBT) on the Adversity Quotient® (AQ®) of the houseparents of CICL. A total of eight houseparent participants completed five-sessions of SFBT. They answered the online AQ Profile® for their pretest/posttest to measure the effect of SFBT on their AQ®. The mean post test score (M=135.00, SD=19.70) is slightly lower than the mean pretest score (M=135.88, SD= 11.66). Based on the Wilcoxon Signed Rank Test Analysis (ƿ> α, 0.779 >0.0.5), there is no significant difference in the AQ® of the houseparents of CICL before and after their exposure to SFBT. However, SFBT as an intervention is an avenue for the houseparents of CICL to share their experience, reduce their stress, learn something, and experience positive change which are reported effects of the intervention." --